SIMONEV: Visual Neonatal Monitoring System - A Dashboard for managing highly complex patients - Salvador Barreix, Iñaki (2021)
In 2019, based on R&D+i work between the Universidad Nacional del Sur and the General Dr. José Penna Interzonal Hospital, a neonatal monitoring system called SIMONE was developed to help reduce the incidence of safety problems in neonatal care. In this article, we present SIMONEV, an extension of SIMONE that integrates a visualization dashboard for the control of patients and critical processes in the hospital’s Neonatal Intensive Care Units. SIMONEV is a free and open-source visualization dashboard that allows the Hospital staff to easily follow statistics and indicators from patients at the neonatal intensive care units. Through this dashboard, a visual representation of statistics, monitoring information, and instrument indicators on patients is presented to the professionals. For this, a series of visualizations were proposed, where data collected by SIMONE is monitored through visual resources and interactions. The proposed software was implemented on the web through technologies such as Angular and Firebase under an open-source policy.